Ethnobotanical Use, Phytochemistry, Pharmacology, and Toxicity of Canavalia gladiata - Qian H; Meng D; Yue L; Xu H; Feng K; Wang J (Drug Design, Development and Therapy)
Huiqin Qian, Di Meng, Lu Yue, Haibo Xu, Kun Feng, Jianan Wang College of Pharmacy, Sanquan College of Xinxiang Medical University, Xinxiang, 453000, People’s Republic of ChinaCorrespondence: Huiqin Qian, College of Pharmacy, Sanquan College of Xinxiang Medical University, Xinxiang, 453000, People’s Republic of China, Email 14522009@sqmc.edu.cnAbstract: Canavalia gladiata (C. gladiata) is a significant traditional Chinese medicine that has been used to treat hiccups, vomiting, nausea, amenorrhea, chronic dysentery, larynx arthralgia, lumbago, and inflammatory diseases in Asia for a long history. Although the chemical composition of C. gladiata has been reported, no thorough review of C. gladiata has been published. Therefore, the present study aimed to comprehensively analyze the ethnobotanical use, phytochemistry, pharmacology, and toxicity of C. gladiata. All the available information on C. gladiata was actualized by systematically searching scientific databases including Web of Science, ScienceDirect, PubMed, Google Scholar, Springer, Wiley, CNKI, CSPD, and Baidu Scholar between 1967 and up-to-date. Based on the reported information, more than 231 components have been identified in C. gladiata, including flavonoids, terpenes, steroids, organic acids, nitrogenous compounds, amino acids, proteins, etc. Crude extracts, fractions, and constituents from C. gladiata show various pharmacological activities, including antioxidant, antitumor, antimicrobial, anti-inflammatory, antiallergic, immunomodulatory, antiobesity, hepatoprotective, antidiabetic, etc. Notably, the immature seeds are poisonous. Besides, modern research reveals that C. gladiata is rich in chemical constituents and pharmacological activities, which are of great research value. However, more in-depth studies including chemical composition, pharmacological mechanism, quality standardisation, toxicology, and clinical research trials are needed for C. gladiata as a new candidate for future drug development.Keywords: ethnobotanical use, phytochemistry, pharmacology, toxicity, Canavalia gladiata